Emergent synergistic lysosomal toxicity of chemical mixtures in molluscan blood cells (hemocytes). (April 2018) - Moore, M.N.; Wedderburn, R.J.; Clarke, K.R.; McFadzen, I.R.B.; Lowe, D.M.; Readman, J.W.
Abstract: The problem of effective assessment of risk posed by complex mixtures of toxic chemicals in the environment is a major challenge for government regulators and industry. The biological effect of the individual contaminants, where these are known, can be measured; but the problem lies in relating toxicity to the multiple constituents of contaminant cocktails. The objective of this study was to test the hypothesis that diverse contaminant mixtures may cause a greater toxicity than the sum of their individual parts, due to synergistic interactions between contaminants with different intracellular targets. Lysosomal membrane stability in hemocytes from marine mussels was used for in vitro toxicity tests; and was coupled with analysis using the isobole method and a linear additive statistical model. The findings from both methods have shown significant emergent synergistic interactions between environmentally relevant chemicals (i.e., polycyclic aromatic hydrocarbons, pesticides, biocides and a surfactant) when exposed to isolated hemocytes as a mixture of 3 & 7 constituents. The results support the complexity-based hypothesis that emergent toxicity occurs with increasing contaminant diversity, and raises questions about the validity of estimating toxicity of contaminant mixtures based on the additive toxicity of single components. Further experimentation is required to investigate the potential for interactive effects in mixtures with more constituents (e.g., 50–100) at more environmentally realistic concentrations in order to test other regions of the model, namely, very low concentrations and high diversity. Estimated toxicant diversity coupled with tests for lysosomal damage may provide a potential tool for determining the toxicity of estuarine sediments, dredge spoil or contaminated soil. Graphical abstract: Evidence for synergistic toxicity as a consequence of increasing diversity of harmful chemicals. Test matrix (circular symbols) for chemical molar concentrations versus chemical diversity (log10 scales) with the % lysosomal toxicity (shaded boxes) shown for the corresponding treatment. The conjectured curve for the subcriticality/supracriticality boundary employs the 50% isoeffective concentrations (open grey diamond shapes) for the 3 mixtures. The 50% additivity concentrations are shown as a dashed line. Image 1 Highlights: Emergent synergistic interactions between toxic chemicals. Toxicity increases with increasing chemical diversity. Toxicant diversity as a potential tool for assessing mixture toxicity. Abstract : Synergistic interactions have been observed in mixtures of toxic chemicals and relatively non-toxic chemicals increase the toxicity of the mixture. Toxicity increases with chemical diversity.